THE FORMATION AND DEVELOPMENT HISTORY OF THE COMMUNICATION SYSTEM IN CENTRAL ASIA IN THE 19TH CENTURY (TAMADDUN NURI JURNALI, 2025)
This article explores the historical formation and developmental stages of the communication system in Central Asia. It examines the role of postal services in state governance, military campaigns, and trade relations in Khorezm and other regions, starting from the medieval period. In particular, the positions of Sohibi a’fol and Sohib bari are analyzed as key elements in the delivery of letters and diplomatic documents, as well as the information exchange system through trade caravans.